Power, Control, and Marital Violence; Beliefs vs. Behavior. A Test of the Graham-Kevan Archer Measure - Emery, Clifton; Wu, Shali; Lee, Hotaek; Yang, Hyerin; Trung, Hai Nguyen; Kim, Jaeyop (International Journal of Criminology and Sociology, 2012)
We argue that Western conceptualizations of a common couple violence/intimate terrorism divide in domestic violence categories may be ill-suited to the Korean context because they are rooted in psychopathological explanations of control motivation (Holtzworth-Munroe & Stuart, 1994; Johnson, 2008). Control motivation in Korea may be more related to the cultural necessity of keeping face in a normatively patriarchal context rather than the attachment issues suggested by Holtzworth-Munroe and Stuart (1994). To examine the power and control context of domestic violence in Korea, we implemented Graham-Kevan and Archer's (2003) measure on a sample of 77 Korean students at an elite university in Seoul. We used cluster analysis to separate the sample into high and low control cluster families. The high control cluster was associated with more domestic violence, more violence by the husband, more injuries from violence, and marginally more child abuse. Contrary to our prediction, being in the high control cluster appears to be a more important predictor of domestic violence than patriarchal beliefs. Implications and limitations are discussed.